Integration of gender in the design process of mechatronic products: An interdisciplinary approach - Holl, Helmut; Horwath, Ilona; Cojocau, Eugenia; Hehenberger, Peter; Ernst, Waltraud (Materialstoday)

Bedarfsorientierte Technikentwicklung und gesell-schaftliche Akzeptanz Das Modell der „Denkschule“ - Horwath, Ilona; Terhechte, Johannes (Dritte Transdisziplinäre Konferenz „Technische Unterstützungssysteme, die die Menschen wirklich wollen“ 2018)
The transdisciplinary approach of the „Denkschule” aims to foster the social relevance, useful-ness and sustainability of engineering concepts and technological development. Drawing on methods of qualitative social research, the „Denkschule” allows to involve, document, analyze, thus to integrate a diversity of types of knowledge, experience and perspectives of participants in order to transfer them into socio-technical innovations. The „Denkschule” offers a dialogue forum for science and the public. In our contribution, we would like to introduce the concept of the „Denkschule”, the applied methods, some selected results, and approaches to transfer results into research and technology development. Currently, these focus on the topics of mobility support and care, rescue and security as well as resource efficiency and climate protection.
Keywords: Interdisziplinarität; Transdisziplinarität; Diversität; Leichtbau; Mobilität

Influence of the Layer Time on the Resulting Part Properties in the Fused Deposition Modeling Process - Knoop, F.; Schöppner, Volker (SPE ANTEC 2018)
The Fused Deposition Modeling (FDM) process by Stratasys is an additive manufacturing (AM) technique that can be used to produce complex thermoplastic parts without the need of a forming tool. A big challenge of this process is that there are several influencing factors with unknown effect on the resulting part properties. One of these factors is the layer time. The aim of this study is to examine the influence of the layer time on the resulting dimensional accuracy and mechanical properties of FDM components manufactured with the amorphous polymer ABS-M30. For this purpose a special job layout was designed to vary the layer time within a certain range. The investigations in this paper show a significant influence on the dimensional accuracy and also on the mechanical properties.

Investigations of High-Speed Rubber Extrusion with Consideration of Melt Homogeneity - Schöppner, Volker; Schadomsky, Michael; Stüker, Daniel (Deutsche Kautschuk-Tagung (DKT 2018))

Functional investigation of zero lead radial shaft seal counter-surfaces turned with a special method - Thielen, Stefan; Magyar, Balázs; Sauer, Bernd; Schneider, Frank; Mayer, Patrick; Kirsch, Benjamin; Müller, Ralf; v. Harbou, Erik; Aurich, Jan C. (Tribology International)
The sealing capabilities of RSS do not only depend on the seal itself but also on the lubricant and the shaft surface. A twist structure on the surface can cause pumping of the fluid during shaft rotation which can result in leakage. In this paper a special, new turning method, which consists of at least two turning steps with feed in reciprocal direction, is presented as an alternative to the conventional manufacturing process. The goal is to create a surface structure with a net pumping rate of zero. Shafts turned with the new proposed method are compared to turned shafts from previous investigations [1]. Criteria for the comparison are the surface pumping rate, leakage and wear behavior of the surface.
Keywords: Radial shaft seals; Turned surfaces; Microstructure

Energieeffizienz im Antriebsstrang bestmöglich ausschöpfen - Sellschop, K; Magyar, Balázs; Oehler, M (Konstruktion)

Experimental Determination and Comparison of the Contact Temperature of Radial Shaft Seals and its Derived Tribological System - Burkhart, C; D, Weyrich; Magyar, Balázs; Sauer, B

Energieeffiziente Federkraftbremse - Schadomsky, Magnus; Zimmer, Detmar; Neumann, Christian (Konstruktion - Zeitschrift für Produktentwicklung und Ingenieur-Werkstoffe)
Die Federkraftbremse ist eine in der elektromechanischen Antriebstechnik häufig eingesetzte Komponente. Ihre Hauptaufgabe besteht darin, bewegliche Lasten im Stillstand zu halten, sowie bei Stromausfall automatisch einen Notstopp einzuleiten. Das Öffnen und Offenhalten der Federkraftbremse erfolgt elektromagnetisch; das Schließen wird durch Druckfedern realisiert. Aufgrund der Kennlinie des Elektromagneten bietet sich hinsichtlich der Energieeffizienz ein nennenswertes Optimierungspotential. Der vorliegende Beitrag beschreibt die systematische Entwicklung eines Funktionsmusters, das bei ähnlichen Stückkosten und geringerem Materialeinsatz insbesondere für die Funktion „Halten“ eine signifikante Reduzierung des Energiebedarfs erreicht.
Keywords: Federkraftbremse; Energieeffizienz

Ein neuer Ansatz zur Modellierung von Transportvorgängen in Füllkörperschüttungen - Salten, Alexander Heinrich Johannes; Maćkowiak, J. F.; Maćkowiak, J.; Kenig, Eugeny
Keywords: PubList

Wear of shaft and seal in an radial shaft seal like tribosystem - Burkhart, C; Emrich, S; Magyar, Balázs; Kopnarski, M; Sauer, B

Sealing contact shaft structure design using EHL simulation - Thielen, S; Foko Foko, F; Magyar, Balázs; Sauer, B

Efficiency calculation of worm gear boxes through coupled tribological and thermal simulation - Oehler, M; Magyar, Balázs; Sauer, B

Combination of Tribological and Thermal Simulation using the Example of Worm Gear Drives - Oehler, M; Magyar, Balázs; Sauer, B

A new standardizable Calculation Method to predict the Efficinecy of Worm Gear Drives - Oehler, M; Magyar, Balázs; Sauer, B (Power Transmission Engineering)

Gekoppelte thermische und tribologische Analyse von Schneckengetrieben - Oehler, M; Magyar, Balázs; Sauer, B (Tribologie und Schmierungstechnik)

EHD Simulation eines Kettengelenkes - Magyar, Balázs; Thielen, S; Löwenstein, M; Becker, A; Sauer, B (Tribologie und Schmierungstechnik)

EHL simulation of the radial shaft sealing system - Thielen, S; Magyar, Balázs; Foko Foko, F; Sauer, B

Untersuchungen zum Wellenverschleiß bei Radialwellendichtringen - Burkhardt, C; Emrich, s; Magyar, Balázs; Sauer, B

Charakterisierung von Schmierstoffen durch Kombination von Experiment und Simulation - Simo Kamga, L; Oehler, M; Magyar, Balázs; Sauer, B

Charakterisierung des strukturviskosen Verhaltens von Schmierstoffen durch Kombination von Experiment und EHD-Simulation mithilfe des Carreau-Modells - Simo Kamga, L; Oehler, M; Magyar, Balázs; Sauer, B (Forschung im Ingenieurwesen)

Processing Short Fiber-reinforced Polymers in the Fused Deposition Modeling Process - Schumacher, Christian; Schöppner, Volker; Gnaase, Stefan (Proceedings of the 29th Annual InternationalSolid Freeform Fabrication Symposium – An Additive Manufacturing Conference)
By adding fibers to a polymer matrix, a reinforcement of the material can be achieved. Shortfiber-reinforced polymers can easily be processed by the Fused Deposition Modeling (FDM)process without major modifications to the processing machine. For instance, short fiber-reinforcedfilaments can be processed to produce short fiber-reinforced components in the FDM process. Inmany other additive manufacturing processes this is not possible at this low cost. The choice of thematrix material, fiber type, fiber length and fiber orientation have a major influence on theproperties of the produced component. In this paper, short fiber-reinforced filaments are processedby the FDM process. The processing properties and the resulting part properties are investigatedwith regard to fiber-specific influences. Additionally, the effects of different strand geometries andthus changed flow fields on the fiber orientation and mechanical part properties are investigated.

Untersuchungen zur induktiven Erwärmung im Warmformprozess - Niewel, Jörg
Keywords: Manganlegierung; Borlegierung; Formhärten; Temperaturverteilung; Blechumformen; Warmumformen; Rollofen; Erwärmung; Induktive Erwärmung; Prozessanalyse; Wirtschaftlichkeit; Kraftfahrzeugbau; Leichtbau; Hochschulschrift

Entwicklung und Analyse neuartiger Verfahrensvarianten zum quasisimultanen Laser-durchstrahlschweißen unter Berücksichtigung der Temperaturentwicklung - Lakemeyer, Patrick

Erweiterung der Modellierung zur Durchsatz- und Leistungsberechnung von Feststoffförderprozessen in der Einschneckenextrusion - Trippe, Jan Klaus

Verfahrensentwicklung zur Einarbeitung nanoskaliger Suspensionen in Polyethylenterephthalat - Wilhelm, Matthias

A least squares approach for effective shear properties in an $${{\varvec{n}}}$$ n -layered sphere model - Mahnken, Rolf; Lenz, Peter; Dammann, Christian (Archive of Applied Mechanics)

Derivation of an n-layered composite sphere model for thermo-chemo-mechanical effective properties - Dammann, Christian; Mahnken, Rolf; Lenz, Peter (PAMM)

Unschärfe in der Simulation im Kontext von Sicherheitsdiskursen - Dridger, Alex; Mahnken, Rolf (Wissenschaft im Angesicht »großer gesellschaftlicher Herausforderungen«)

Transformation strains for bainitic variant evolution in steel - Ehlenbröker, Ulrich; Petersmann, Manuel; Antretter, Thomas; Mahnken, Rolf (PAMM)

The effective shear modulus for ann-layered composite sphere - Lenz, Peter; Dammann, Christian; Mahnken, Rolf (PAMM)

A multi-mechanism model for cutting simulation: A Ginzburg-Landau type phase gradient and numerical implementations - Cheng, C.; Mahnken, Rolf (International Journal of Solids and Structures)

Possibilistic and stochastic analysis using for rubber‐like materials - Penner, Eduard; Caylak, Ismail; Dridger, Alex; Mahnken, Rolf (PAMM)

A multivariate stochastic material model with correlated material parameters - Penner, Eduard; Caylak, Ismail; Mahnken, Rolf (PAMM)

Modellbasierter Entwurf intelligenter mechatronischer Systeme mithilfe semantischer Technologien - Oestersötebier, Felix

Large Scale Thermodynamic Data Generation with Molecular Simulation - Rutkai, Gábor

Effiziente bruchmechanische Herangehensweise für eine wirtschaftliche Produktentstehung und einen sicheren Bauteilbetrieb - Grübel, Alexander

3D-Risswachstum in homogenen, isotropen sowie funktional gradierten Strukturen - Dibblee, Katharina

Confinement Induced Segregation Effects in Suspension Rheology - Pieper, Sven

Entwicklung einer Prozesskette zum flüssig-flüssig Phasentransfer nanoskaliger Partikeln - Grimm, Philipp

Zur Modellierung von Kapillarbrücken zwischen nanoskaligen Partikeln - Dörmann, Michael

Untersuchungen zum methodenbasierten Prozessverständnis des radialsymmetrischen Schneidclinchens - Hörhold, Réjane

Automatisierte Variantenreduzierung durch virtuelle Verbindungsauslegung beim Halbhohlstanznieten - Menne, Franz Ferdinand

Entwicklung eines lokal wirkenden Oberflächenreinigungsprozesses zur Erhöhung der Prozessfähigkeit beim Aluminiumlichtbogenbolzenschweißen - Reis, Christian

Prüfkonzept zur Kennwertermittlung für geklebte FVK/Metall-Verbindungen - Wünsche, Marc André

Robuste Auslegung und Berechnung struktureller Klebverbindungen unter Crashbelastung - Schwarzkopf, Georg

Einstufiges Widerstandselementschweißen für den Einsatz im Karosseriebau - Wiese, Lars

Systematic Approach for Cost Efficient Design and Planning with Additive Manufacturing - Lindemann, Christian-Friedrich Wilhelm

Analysis of fluid dynamics and heat transfer in pillow-plate heat exchangers - Piper, Mark

Elektrochemische Korrosionsprüfung - Ditz, Michael; Meschut, Gerson; Grothe, Richard; Grundmeier, Guido; Windoffer, Marcel; Kötting, Gerhard (adhäsion KLEBEN & DICHTEN)
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Temperaturbedingte Relativverschiebung von Dickschichtklebungen - Mailänder, Sebastian; Meschut, Gerson (adhäsion KLEBEN & DICHTEN)
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Design of elastic adhesive bonds - Mailänder, Sebastian; Meschut, Gerson (ADHESION ADHESIVES&SEALANTS)
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Optimization of Tooling Design for Hot Mandrel Bending of Pipe Elbows - Diekmann, Uwe; Homberg, Werner; Prehm, Jens; Rostek, Tim; Schönhoff, Nils; Tabakajew, Dmitri; Trasca, Andreea; Uysal, Haris (Materials Science Forum)
This paper presents the finite element model developed for the simulation of pipe elbow production by the so-called ‘Hamburg process’ in order to improve productivity and resource efficiency. To optimize the tooling design, a sensitivity analysis of the tool parameters that influence the quality of pipe elbows, such as mandrel height and length, is conducted. Different materials data sets including damage models were considered. Using numerical simulations, it is possible to determine an optimized tool geometry for the production of specific pipe elbow dimensions. Furthermore, as a result of the experiments and numerical simulations conducted, it is possible to increase the production velocity of the serial plant. Along with deformation, damage models are included in simulations in order to identify the right process boundaries. Finally, an experimentally validated model is developed for increasing resource efficiency in pipe elbow fabrication.

Grading Technologies for the Tanufacture of Innovative Cutting Blades - Rostek, Tim; Homberg, Werner (AIP Conference Proceedings 1960, 100013)

Hybride Verbundstrukturen aus Aluminium und Titan für Leichtbauanwendungen - Homberg, Werner; Rostek, Tim; Schaper, Mirko; Grydin, Olexandr; Andreiev, Anatolii; Brosius, Alexander; Guilleaume, Christina

Konstruktionsrichtlinien für eine softwaregestützte Anpassung von additiv gefertigten Bauteilen im Hinblick auf eine robuste Fertigung - Lammers, Stefan; Tominski, Johannes; Magerkohl, Sebastian; Künneke, Thomas; Lieneke, Tobias; Zimmer, Detmar (Proceedings of the 15th Rapid.Tech Conference)
Neue Konstruktionsabläufe und Potentiale bei der Gestaltung additiv hergestellter Bauteile verlangen insbesondere im Konstruktionsprozess ein Umdenken. Fehlende Kenntnisse über die additive Fertigungstechnologie hemmen zusätzlich dieses Umdenken [HHD06, WC15]. Um die verhältnismäßig neue Fertigungstechnologie zugänglicher zu machen, wurden in den letzten Jahren verschiedene Konstruktionsempfehlungen erarbeitet. Die Vielzahl an Empfehlungen erschwert dem Konstrukteur allerdings einen entsprechenden Überblick zu behalten und für ihn relevante von nicht relevanten Empfehlungen zu sondieren. Aus diesem Grund wurden öffentlich zugängliche Empfehlungen für das Laser-Strahlschmelzen zusammengetragen und einer Priorisierung unterzogen. Das Ergebnis beinhaltet Konstruktionsempfehlungen, die einen relevanten Einfluss auf die Bauteilfertigung, die Bauteilqualität und -funktion haben. Durch Abstraktion dieser Empfehlungen konnten Richtlinien erarbeitet werden, die für eine softwareseitige Gestaltprüfung verwendet werden können. Durch diese Gestaltprüfung können Bauteile beliebiger Komplexität, zum Beispiel feine Gitter oder topologieoptimierte Strukturen, bereits vor der Fertigung hinsichtlich der Einhaltung relevanter Konstruktionsrichtlinien überprüft werden. Der Gestaltprüfer greift dabei auf eine Datenbank zurück, die zulässige, quantitative Grenzwerte von Konstruktionsrichtlinien enthält. Diese Grenzwerte werden im Folgenden Attributsausprägungen genannt und können experimentell ermittelt werden. Hierfür wurden standardisierte Prüfkörperbaujobs entwickelt, die alle notwendigen Prüfkörper zur Ermittlung der Attributsausprägungen enthalten und deren Auswertung eine Erweiterung der Datenbank hinsichtlich

Design Guidelines for a Software-supported Adaptation of Additively Manufactured Components with Regard to a Robust Production - Lammers, Stefan; Tominski, Johannes; Magerkohl, Sebastian; Lieneke, Tobias; Künneke, Thomas; Zimmer, Detmar (29th Annual International Solid Freeform Fabrication Symposium)
The design of additively manufactured components requires a rethinking in the design process. This is inhibited by a lack of knowledge about additive manufacturing technologies. For this reason, a large number of design guidelines have been developed in recent years. In their present form the design guidelines are not suitable for processing in a software algorithm, since the guidelines have a certain redundancy and partly influence each other. This paper describes several steps to consolidate the existing guidelines and to prepare them in a way that they can be used in a software algorithm for a design check. Therefore, existing guidelines are collected, prioritized and quantified with regard to their relevance for a robust production. To quantify the guidelines, test specimens are developed, produced and evaluated in order to obtain a limit value for the geometric properties. With these limit values, quantifiable design guidelines can be applied to designers and software tools.

Analysis of the interaction between the temperature field and the weld seam morphology in laser transmission welding by using two different discrete laser wavelengths - Schöppner, Volker; Lakemeyer, Patrick; Geißler, Bastian; Laumer, Tobias; Wübbeke, Andrea; Frick, Thomas (Journal of Laser Applications)

Analysis of the weld seam morphology of polypropylene in laser transmission welding - Schöppner, Volker; Wübbeke, Andrea; Geißler, B.; Laumer, T.; Frick, T.; Schmidt, M. (Manuf. Sci. Eng)

Herstellung innovativer Stahlhalbzeuge mit wanddicke- und festigkeitsveränderlichen Eigenschaften für den Leichtbau durch Innendrückwalzen (IDW) - Wiens, Eugen; Homberg, Werner

Internal Flow-Turning – extended manufacturing possibilities in tailored tube production - Wiens, Eugen; Homberg, Werner (MATEC Web of Conferences)

FROM EMPOWERMENT TO INNOVATION: INTER- AND TRANSDISCIPLINARY RESEARCH METHODS IN LIGHTWEIGHT ENGINEERING - Horwath, Ilona; Dohmeier-Fischer, Silvia; Weiß-Borkowski, Nathalie; Tröster, Thomas (INTED2018 Proceedings)

Inline additively manufactured functionally graded multi-materials: microstructural and mechanical characterization of 316L parts with H13 layers - Hengsbach, Florian; Koppa, Peter; Holzweissig, Martin Joachim; Aydinöz, Mehmet Esat; Taube, Alexander; Hoyer, Kay-Peter; Starykov, Oleksiy; Tonn, Babette; Niendorf, Thomas; Tröster, Thomas; Schaper, Mirko (Progress in Additive Manufacturing)

Selective Laser Melting of Ti6Al4V with High Build Rates and Following Hot Isostatic Pressing - Ahlers, Dominik; Tröster, Thomas; Hermann, S.; Koppa, P.; Gloetter, P.; Schaper, Mirko; Peters, M.; Burns, M.; Hengsbach, F.; Altmann, A. (Contributed Papers from MS&T17)

NEW APPROACHES IN LIGHTWEIGHT DESIGN: V-MODEL OF LIGHTWEIGHT DESIGN BY COMPOSITES AS AN APPROACH OF INTER- AND TRANSDISCIPLINARY RESEARCH - Weiß-Borkowski, Nathalie; Horwath, Ilona; Berscheid, A.; Dohmeier-Fischer, Silvia; Tröster, Thomas (INTED2018 Proceedings)

Design and Testing of Co-Cured Bonded CFRP-Steel Hybrids with Nanostructured Interfaces for Interlaminar Fracture Toughness - Striewe, Jan André; Grothe, R.; Kowatz, Jannik; Tröster, Thomas; Grundmeier, Guido; Meschut, Gerson

LHYBS – Lightweight Design by Novel Hybrid Materials - Camberg, Alan Adam; Tröster, Thomas; Heggemann, Thomas; Homberg, H.; Schaper, Mirko; Dietrich, J.; Bremser, Wolfgang; Achterberg, L.; Kabst, M.; Wille, M.; Peckhaus, Volker

Forming and corrosion stability of a laser pre-treated metal surface-influence on the properties of metal-CFRP hybrid structures made by VARTM - Zinn, C.; Wang, Z.; Tröster, Thomas; Schaper, Mirko

Inline additively manufactured functionally graded multi-materials: microstructural and mechanical characterization of 316L parts with H13 layers - Hengsbach, Florian; Koppa, Peter; Holzweissig, Martin Joachim; Aydinöz, Mehmet Esat; Taube, Alexander; Hoyer, Kay-Peter; Starykov, Oleksiy; Tonn, Babette; Niendorf, Thomas; Tröster, Thomas; Schaper, Mirko (Progress in Additive Manufacturing)

Inline additively manufactured functionally graded multi-materials: microstructural and mechanical characterization of 316L parts with H13 layers - Hengsbach, Florian; Koppa, Peter; Holzweissig, Martin Joachim; Aydinöz, Mehmet Esat; Taube, Alexander; Hoyer, Kay-Peter; Starykov, Oleksiy; Tonn, Babette; Niendorf, Thomas; Tröster, Thomas; Schaper, Mirko (Progress in Additive Manufacturing)
Keywords: Industrial and Manufacturing Engineering

Anodizing of electrolytically galvanized steel surfaces for improved interface properties in fiber metal laminates - Engelkemeier, Katja; Mücke, Christian; Hoyer, Kay-Peter; Schaper, Mirko (Advanced Composites and Hybrid Materials)
Keywords: Materials Chemistry; Polymers and Plastics; Materials Science (miscellaneous); Ceramics and Composites

Influence of sp3/sp2-carbon ratio of vertically standing carbon nanostructures produced by pulsed laser-treatment on PAN-based carbon fibers - Engelkemeier, Katja; Hoyer, Kay-Peter; Schaper, Mirko (Materials Letters)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Anodizing of electrolytically galvanized steel surfaces for improved interface properties in fiber metal laminates - Engelkemeier, Katja; Mücke, Christian; Hoyer, Kay-Peter; Schaper, Mirko (Advanced Composites and Hybrid Materials)

Influence of sp3/sp2-carbon ratio of vertically standing carbon nanostructures produced by pulsed laser-treatment on PAN-based carbon fibers - Engelkemeier, Katja; Hoyer, Kay-Peter; Schaper, Mirko (Materials Letters)

Shear strength and failure behaviour of laser nano-structured and conventionally pre-treated interfaces in intrinsically manufactured CFRP-steel hybrids - Zinn, Carolin; Bobbert, Mathias; Dammann, Christian; Wang, Zheng; Tröster, Thomas; Mahnken, Rolf; Meschut, Gerson; Schaper, Mirko (Composites Part B: Engineering)

Water Quenching of Hot-Rolled Aluminum Strips: Process Integrated Heat Treatment of the Alloy EN AW-6082 - Grydin, Olexandr; Andreiev, Anatolii; Sotirov, Nikolay; Stolbchenko, Mykhailo; Behr, Teresa M.; Ashkelianets, Anton; Frolov, Iaroslav; Schaper, Mirko (JOM)

Friction-spinning—Grain structure modification and the impact on stress/strain behaviour - Lossen, Benjamin; Andreiev, Anatolii; Stolbchenko, Mykhailo; Homberg, Werner; Schaper, Mirko (Journal of Materials Processing Technology)

Graphene oxide as flexibilizer for epoxy amine resins - Wolk, Andreas; Rosenthal, Marta; Weiß, Julia; Voigt, Markus; Wesendahl, Jan-Niklas; Hartmann, Marc; Grundmeier, Guido; Wilhelm, Rene; Meschut, Gerson; Tiemann, Michael; Bremser, Wolfgang (Progress in Organic Coatings)
Different types of reduced graphene oxide and graphene oxide particles have been studied regarding their influence on the curing behaviour of epoxy-amine resins. Especially the specific surface area of reduced graphene oxide was selectively influenced by controlled drying of the material. The different types of reduced graphene oxide particles were used to produce epoxy-amine composites that significantly change their curing behaviour and mechanical properties. A variety of surface areas and compositions were prepared by combination of a fast heating rate and different drying methods. The combination of freeze drying with a fast heating rate leads to a large specific surface area of 680 m2/g. The morphologies of the particles were observed by scanning electron microscope and the BET surface area was measured with nitrogen-physisorption. The exfoliation quality was measured by XRD. The generated graphene oxide and thermally reduced graphene oxide particles were mixed with epoxy-amine resin. The curing behaviour was studied with rheological and differential scanning calorimetry (DSC) measurements. We observed that different surface functionalities lowers the Glass transition temperature and the gel time of an epoxy-amine curing system. In addition, we found that generated graphene oxide acts as flexibilizer. An increase of the deformation from 2.5 mm to 3.1 mm was measured by Erichsen Cupping Test.

Shear-Clinching of Multi-Element Specimens of Aluminium Alloy and Ultra-High-Strength Steel - Han, Daxin; Hörhold, Réjane; Müller, Martin; Wiesenmayer, Sebastian; Merklein, Marion; Meschut, Gerson (Key Engineering Materials)
The newly developed joining-by-forming technology “shear-clinching”, features a potentially single-stage process for joining UHSS without requiring any additional elements. Foundational studies have focused on the functionality of shear-clinching at a one-element sample. To ensure the safety of the industrial application of the shear-clinching technology, an investigation with component-like samples with several joints is required. This paper presents a detailed analysis of the material behaviour during the shear-clinching process with multi-element specimens to evaluate the influence of the neighbouring joints. In order to describe the influence of the neighbouring joints, the deformations resulting from the bending and material displacement are recorded without contact after the joining process: locally around the joining point and globally over the entire sample size. To minimize such bending effects, a tool-sided adaptation is provided. The results show the high potential of shear-clinching joining by UHSS and give further recommendations for future multi-material application.

Application of self-piercing nuts during hot forming of 22MNB5 - Meyer, Sebastian; Meschut, Gerson; Vogt, Hendrik; Behrens, Bernd-Arno; Hübner, Sven; Neumann, André (Welding in the World)

Prüfkonzept für geklebte Stahl/CFK-Strukturen - Meschut, Gerson; Teutenberg, Dominik; Wünsche, Marc (adhäsion KLEBEN & DICHTEN)

Funktionsintegration in der Warmblechumformung - Meyer, Sebastian; Meschut, Gerson; Behrens, Bernd-Arno; Vogt, Hendrik; Neumann, Andre (Werkstattstechnik online)

Optimization-based reliability control of mechatronic systems - Meyer, Tobias
Reliability-adaptive systems allow an adaptation of system behavior based on current system reliability. They can extend their lifetime at the cost of lowered performance or vice versa. This can be used to adapt failure behavior according to a maintenance plan, thus increasing availability while using up system capability fully. To facilitate setup, a control algorithm independent of a degradation model is desired. A closed loop control technique for reliability based on a health index, a measure for system degradation, is introduced. It uses self-optimization as means to implement behavior adaptation. This is based on selecting the priorities of objectives that the system pursues. Possible working points are computed beforehand using model-based multiobjective optimization techniques. The controller selects the priorities of objectives and this way balances reliability and performance. As exemplary application, an automatically actuated single plate dry clutch is introduced. The entire reliability control is setup and lifetime experiments are conducted. Results show that the variance of time to failure is reduced greatly, making the failure behavior more predictable. At the same time, the desired usable lifetime can be extended at the cost of system performance to allow for changed maintenance intervals. Together, these possibilities allow for greater system usage and better planning of maintenance.
Keywords: dependability; reliability; behavior adaptation; self-optimization; multiobjective optimization; optimal control; automotive drivetrain; clutch system; reliability-adaptive system

A Reinforcement Learning Strategy for the Swing-Up of the Double Pendulum on a Cart - Hesse, Michael; Timmermann, Julia; Hüllermeier, Eyke; Trächtler, Ansgar (Procedia Manufacturing)
The effective control design of a dynamical system traditionally relies on a high level of system understanding, usually expressed in terms of an exact physical model. In contrast to this, reinforcement learning adopts a data-driven approach and constructs an optimal control strategy by interacting with the underlying system. To keep the wear of real-world systems as low as possible, the learning process should be short. In our research, we used the state-of-the-art reinforcement learning method PILCO to design a feedback control strategy for the swing-up of the double pendulum on a cart with remarkably few test iterations at the test bench. PILCO stands for “probabilistic inference for learning control” and requires only few expert knowledge for learning. To achieve the swing-up of a double pendulum on a cart to its upper unstable equilibrium position, we introduce additional state restrictions to PILCO, so that the limited cart distance can be taken into account. Thanks to these measures, we were able to learn the swing up at the real test bench for the first time and in only 27 learning iterations.

Approaches on How to analyse Terms and Definitions Applied in the Domain of Crisis and Disaster Management - Neubauer, Georg; Rainer, Karin; Pottebaum, Jens; Knesic, Snjezana; Baucic, Martina (IDIMT-2018. Strategic modeling in management, economy and society : 26th Interdisciplinary Information Management Talks, Band 47)

Influence Factors for Innovation in Digital Self-Preparedness Services and Tools - Gräßler, Iris; Pottebaum, Jens; Scholle, Philipp (International Journal of Information Systems for Crisis Response and Management)

Optimization of the energy supply in the plastics industry to reduce the primary energy demand - Dunkelberg, Heiko; Wagner, Johannes; Hannen, Conrad; Schlüter, Alexander; Phan, Long; Hesselbach, Jens; Lin, Cheng-Xian (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment

Der Chatbot im Kundenservice der Energiewirtschaft - Schlüter, Alexander

Lifetime Extension of Photovoltaic Modules by Influencing the Module Temperature Using Phase Change Material - Weber, Daniel; Rafsan Jani, Mohammad Iffat; Grabo, Matti; Wallscheid, Oliver; Klaus, Tobias; Krauter, Stefan; Böcker, Joachim (World Conference on Photovoltaic Energy Conversion (WCPEC-7), 45th IEEE PVSC, 28th PVSEC, 34th EU PVSEC.)

Additive Manufacturing of a Soft Magnetic Rotor Active Part and Shaft for a Permanent Magnet Synchronous Machine - Urbanek, Stefan; Ponick, Bernd; Taube, Alexander; Hoyer, Kay-Peter; Schaper, Mirko; Lammers, Stefan; Lieneke, Tobias; Zimmer, Detmar (2018 IEEE Transportation Electrification Conference and Expo (ITEC))

Erarbeitung von Konstruktionsregeln für Hybridbauteile: Integration von metallischen Einlegern in FDM-Strukturen - Schöppner, Volker; Knoop, F.; Köhler, M.; Lieneke, Tobias; Zimmer, Detmar (Konstruktion)

Additive Fertigung nach Maß - Schöppner, Volker; Zimmer, Detmar; Knoop, Frederick; Lieneke, Tobias (Kunststoffe)

Entwicklung einer neuartigen Fügetechnik für Organoblech-Hybridverbindungen - Moritzer, Elmar; Budde, Christopher; Hüttner, Matthias; Krassmann, Dimitri

Mechanical properties of repair welded joints for automobile body structures - Ditter, Jan; Wünsche, Marc; Meschut, Gerson; Wibbeke, Tim Michael

Anforderungsgerechte Analyse instationärer Zustände bei der Verarbeitung von Zweikomponentenklebstoff - Meschut, Gerson; Ernstberger, Ludmila; Ditter, Jan (Schweißen und Schneiden)

Joining TWIP-Steel Simulation Models - Folgar, Ribadas H.; Böddeker, T.; Chergui, A.; Ivanjko, Martin; Gili, F.; Behrens, S. (Procedia Structural Integrity)

JoiningTWIP – TWIP-steels for multi material design in automotive industry using low heat joining technologies II - Böddeker, Tobias; Ivanjko, Martin; Chergui, Azeddine; Gili, Flavia; Behrens, Sabine; Runkel, Dirk; Mašek, Martin (7. Fügetechnisches Gemeinschaftskolloquium)

Corrosion properties of bioresorbable FeMn-Ag alloys prepared by selective laser melting - Wiesener, Markus; Peters, K.; Taube, Alexander; Keller, Adrian; Hoyer, Kay-Peter; Niendorf, Thomas; Grundmeier, Guido (Materials and Corrosion)

Numerische und mechanische Untersuchung additiv gefertigter TiAl6V4 Gitterstrukturen - Taube, Alexander; Reschetnik, Wadim; Pauli, Lorenz; Hoyer, Kay-Peter; Kullmer, Gunter; Schaper, Mirko (Additive Fertigung von Bauteilen und Strukturen)

Optimierung der Werkstoffeigenschaften von selektiv lasergeschmolzenem Alumi-nium 7075, - Brüggemann, Jan-Peter; Reschetnik, Wadim; Kullmer, Gunter; Richard, Hans Albert; Aydinöz, Mehmet Esat; Hoyer, Kay-Peter; Schaper, Mirko (DVM - Tagung - Bruchmechanische Werkstoff- Und Bauteilbewertung: Beanspruchungsanalyse, Prüfmethoden und Anwendungen)

Bonding of wood-plastic composites (WPC)—material and surface modification for special applications - Moritzer, Elmar; Hopp, Matthias (Welding in the World)